1965
DOI: 10.1071/ch9651589
|View full text |Cite
|
Sign up to set email alerts
|

Internal conversion in aromatic and N-heteroaromatic molecules

Abstract: A previous semi-empirical approach to the calculation of the rate of internal conversion, regarded as a tunnelling process, is reformulated on a sounder theoretical basis. Following Robinson and Frosch, tunnelling rates are correlated with Franck-Condon factors for the associated transition. The total Franck-Condon factor, S2max, is a product of three terms, associated respectively with skeletal stretching, CH stretching, and skeletal angle bending vibrations. The value of S2max may be controlled by one term o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
0

Year Published

1969
1969
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…Deuteration is know to greatly decrease the rate of radiationless transitions 72 and it has been shown that skeletal bending and stretching vibrations are important participants in the internal conversion of aromatic nitrogen heterocycles. 73 This observation may be consistent with an IC-mediated process.…”
supporting
confidence: 77%
“…Deuteration is know to greatly decrease the rate of radiationless transitions 72 and it has been shown that skeletal bending and stretching vibrations are important participants in the internal conversion of aromatic nitrogen heterocycles. 73 This observation may be consistent with an IC-mediated process.…”
supporting
confidence: 77%
“…One negative aspect in several cases of stated theories [32,35,37,40,41] is the assumption that vibrational relaxation is rapid compared with radiationless transition rates. Thus, the slower processes, e.g., S1 S0 and S1 T1 and T1 S0 are covered by their theories, but not Sn -S1 or Tn T1 .…”
Section: Kashamentioning
confidence: 99%
“…In this case also ultrafast lasers have a role in defining the mechanism of excitation in specific cases. Not only is this of interest in the case of aromatic hydrocarbons, in which there is an observable competition between S1 and T1 state excitations [16,32], but the case of N-heteromatic molecules poses additional complexities in competitive excitation dynamics [35].…”
Section: Kashamentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that to obtain Eq. (8), we assumed that the change in normal frequencies between the two electronic states is negligible and that the normal vibration is harmonic, assumptions that are reasonable for the A,0g 992 cm-' mode (11,12).…”
mentioning
confidence: 99%